Questões sociais : arte e contextos - Monari, Ana Claudia (2019)
This article presents actions developed in a municipal public school, located in the West region Catarinense / Brazil. The practice was aimed at fostering debates involving social issues in the students’ environment, establishing relationships with contemporary Art and Artists